Completing the life cycle of a broadcast spawning coral in a closed mesocosm. Issue 3 (2nd July 2020) - Craggs, Jamie; Guest, James; Davis, Michelle; Sweet, Michael
ABSTRACT: Studies of broadcast spawning in corals are fundamental to our understanding of early life history characteristics, reproductive biology, restoration etc. Spawning of corals for research is routinely conducted, but this is mostly restricted to sites adjacent to reefs and from broodstock collected from the wild just prior to gamete release. Only recently has it been possible to induce predictable broadcast spawning in an ex situ environment, and nobody has successfully closed the life cycle (i.e., production of an F2 generation) of these corals. Here, for the first time, we closed the life cycle of the broadcast spawning coral Acropora millepora in a fully closed ex situ mesocosm. This breakthrough has numerous implications for our understanding of reproductive biology, specifically it offers potential to deepen our understanding of the genetic influence on adaptive traits such as heat tolerance, growth and disease resistance over multiple generations.